Photosynthetic and ascorbate-glutathione metabolism in the flag leaves as compared to spikes under drought stress of winter wheat (Triticum aestivum L.) - Lou, Lili (PLoS One, 2018)
Ascorbate-glutathione (ASA-GSH) cycle is a major pathway of H(2)O(2) scavenging and an effective mechanism of detoxification in plants. The differences in photosynthesis, chlorophyll content (Chl), relative water content (RWC), antioxidants and antioxidative enzyme activities involved in ASA-GSH metabolism were measured between the flag leaves and spike bracts (glumes and lemmas) during grain filling under drought stress. The expression of APX1, GRC1, DHAR, MDHAR, GPX1, and GS3 in ASA-GSH cycle was also measured. Compared with the flag leaves, the spike bracts exhibited stable net photosynthetic rate (P(N)) and chlorophyll content (Chl), a lower accumulation of reactive oxygen species (ROS), and more enhanced percentages of antioxidant enzyme activities and key enzymes gene transcription levels involved in ASA-GSH metabolism during the grain-filling stage under drought conditions. This could be the reasonable explanation for the more stable photosynthetic capacity in spikes, and the glumes and lemmas senesced later than the flag leaves at the late grain-filling stage. Also, the function of ASA-GSH cycle could not be ignored in alleviating oxidative damage by scavenging more excess ROS in spikes under drought stress.